Not One of the Family: Foreign Domestic Workers in Canada - Bakan, Abigail B.; Stasiulis, Daiva K. (University of Toronto Press, 1997)
In [this book], experts on foreign domestic workers and workers-turned-activists document how the Canadian system has institutionalized unequal treatment of citizen and non-citizen workers. Since the 1940s, rights of citizenship for immigrant domestic workers in Canada have declined while the number of women recruited from Third World countries to work in Canadian homes has dramatically increased. The analysis...is both theoretical and practical, framing ideologies of privacy, maternalism, familialism, and rights, as well as examining government policy, labour organizing, and strategies to resist exploitation. –Publisher's description. Contents: Introduction / Abigail B. Bakan and Daiva Stasiulis – Foreign domestic worker policy in Canada and the social boundaries of modern citizenship / Abigail B. Bakan and Daiva Stasiulis – From mothers of the nation to migrant workers / Sedef Arat-Koc – An affair between nations: international relations and the movement of household service workers / Patricia M. Daenzer – Little victories and big defeats : the rise and fall of collective bargaining rights for domestic workers in Ontario / Judy Fudge – The work at home is not recognized: organizing domestic workers in Montreal / Miriam Elvir – We can still fight back: organizing domestic workers in Toronto / Pura M. Velasco.
Book available at Internet Archive to people with print disabilities: https://archive.org/details/notoneoffamilyfo0000unse